Prospects for the development of the Eurasian Economic Union transport projects and methods of their scientific analysis and monitoring - A. A. Chepkov (Вестник университета, 2025)
The Eurasian Economic Union is one of the key areas for the development of economic, trade and transport cooperation in the Eurasia region. By conducting a comparative analysis of transport system integration with international markets, we should assess potential risks and opportunities associated with the expansion of economic cooperation. Special attention is paid to innovative solutions in logistics and development of transport corridors that can improve the efficiency of the freight. The article presents an analysis of the state of the transport industry in the member states of the Union and key issues of the development strategy of their projects as well as a number of recommended scientific methods for studying the project activities and monitoring methods. Analysis of statistics on the basis of open sources is conducted, and conclusions on the prospects for the development of the projects are given. The article substantiates the need for further research into the effectiveness of the proposed methodologies and strategies for successful implementation of the projects in the long term involving the countries bordering the Union. The results of the study may be useful for government agencies and private sector in planning and implementing transport projects aimed at strengthening economic ties in the Eurasian region.